Introduction - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Verlag, 2019)
This chapter briefly describes a general overview on the sport of archery, the performance parameters influencing the sport, the employment of machine learning in sporting activities, the clustering technique as well as a brief introduction of the machine learning techniques utilised in the present study. The participants are considered, and also the archery shooting test is presented. © 2019, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.